An ethno botanical perspective of traditional medicinal plants from the Khattak tribe of Chonthra Karak, Pakistan. (13th May 2015) - Rehman, Khalid; Mashwani, Zia-ur-Rehman; Khan, Mubark Ali; Ullah, Zahid; Chaudhary, Hassan Javed
Abstract: Ethno pharmacological relevance: The present study was carried out with an aim to gather, evaluate and analyze the ethno botanical information of medicinal uses of the plant species possessed by the native Khattak tribe of the Chonthra, district Karak Pakistan. The region with poor documentation of traditional knowledge, preserving the local traditional knowledge, reporting new as well as rarely reported medicinal properties of medicinal plants, to be tested experimentally for validation. Material and method: The medicinal uses of existing plant species were documented by oral communication with 103 people, all over above 60 years of age, born and residing in Chonthra. Information was gathered by semi-structured interviews with further analysis by indices like Relative frequency citation RFC and Medicinal use value MUV. Results: The study resulted with medicinal information on 66 plants species belonging to 34 families (using against 58 health related problems with 83 different preparations mainly administered orally and topical). The dominant families include Brasicaceae and Limiaceae. Withania coagulans and Pegnum harmala were the plant species quoted 100% by the informants with RFC values 1 each. The MUV were scattered between 1.24 and 0.03. The highest MUV were W. coagulans 1.24, Pegnum harmala 1.18, Fagonia cretica 1.14. This study for the first time include Nepeta lagopsis to the ethnobotanical wealth. Conclusions: This study was an extension to the ethnobotanical research conducted in Khyber Pakhtunkhwa (KPK) Pakistan. The target area being small and less number of plants with limited traditional knowledge can serve basis for further work focusing on rarely or non- reported plant species of pharmacological and phytochemical importance with active metabolite capable of broadening the sources of new drugs. Graphical abstract: